Seeking security or seeking pleasure in sexual behavior? Examining how individual motives shape condom use attitudes - Rodrigues, D. L. (2023)
Research has consistently shown that motives for security (i.e., prevention focus) or pleasure (i.e., promotion focus) determine risk perception and behaviors in several domains, including sexual health. We tested if being more focused on prevention or promotion was associated with condom use attitudes and if the perceived risk of HIV infection explained these associations. Participants (N = 405, 61.7% women; Mage = 23.10, SD = 5.06) took part in an online cross-sectional study. We found positive associations between both regulatory foci and condom use attitudes. Mediation analyses also showed that participants who were more focused on prevention perceived condoms as more reliable, attributed less stigma to condom use, and were less embarrassed about condom use negotiation. These associations were explained by the perception of less risk of HIV infection. Results also revealed a few associations with personality traits and moderations by age and gender. These findings highlight the importance of considering individual motives to gain an understanding of how the perceived risk of infection can shape sexual health decision-making.